2012
DOI: 10.1007/s10103-012-1066-7
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effects of low-level laser therapy on the morphology and oxidative response in the skin wound healing in rats

Abstract: This study aims to investigate the effect of different energy densities provided by low-level laser therapy (LLLT) on the morphology of scar tissue and the oxidative response in the healing of secondary intention skin wounds in rats. Twenty-four male adult Wistar rats were used. Skin wounds were made on the backs of the animals, which were randomized into three groups of eight animals each as follows, 0.9% saline (control); laser GaAsAl 30 J/cm(2) (L30); laser GaAsAl 90 J/cm(2) (L90). The experiment lasted 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 38 publications
1
41
0
3
Order By: Relevance
“…Vascular photomodulation can be associated with the reduction of inflammatory cells and stimulation of macrophages, Tlymphocytes, endothelial cells, and fibroblast migration during the healing process, resulting in accelerated tissue healing [38]. Gonçalves et al showed that the GaAsAl laser applied with an energy density of 60 J/cm 2 was more effective in stimulating neoangiogenesis than 30 J/cm 2 [37]. Furthermore, Corazza et al reported that a dose of 20 J/cm 2 effectively increased fibroblast proliferation and neoangiogenesis in skin wounds [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular photomodulation can be associated with the reduction of inflammatory cells and stimulation of macrophages, Tlymphocytes, endothelial cells, and fibroblast migration during the healing process, resulting in accelerated tissue healing [38]. Gonçalves et al showed that the GaAsAl laser applied with an energy density of 60 J/cm 2 was more effective in stimulating neoangiogenesis than 30 J/cm 2 [37]. Furthermore, Corazza et al reported that a dose of 20 J/cm 2 effectively increased fibroblast proliferation and neoangiogenesis in skin wounds [39].…”
Section: Discussionmentioning
confidence: 99%
“…An adequate blood perfusion is essential to guarantee injured tissue regeneration and, consequently, the success of the repair procedure [37]. Vascular photomodulation can be associated with the reduction of inflammatory cells and stimulation of macrophages, Tlymphocytes, endothelial cells, and fibroblast migration during the healing process, resulting in accelerated tissue healing [38].…”
Section: Discussionmentioning
confidence: 99%
“…The balance between oxidants and antioxidants is directly related to the time and quality of the wound healing process[127]. This process can be divided in four overlapping phases: hemostasis, inflammation, proliferation and remodeling or resolution.…”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
“…The picrosirius red staining-polarization method can distinguish and determine the level of types I and III collagen and has been used for many tissues, such as skin [34], [35], lung [36], cartilage [37], periodontal ligament [38], vocal ligament [39], and tendon [19], [40]. As described in our previous study [18], the type I and III collagen contents in the mid-substance of the ligament were determined by this method.…”
Section: Methodsmentioning
confidence: 99%